Local Anaesthetic Effect of Methanolic Leaves Extract of Lannea schimperi (Hoschst. Ex Rich) Eng - G. Mikail, Hudu; D. Akumka, David; Adamu, Muhammed (Recent Patents on Biotechnology, 2016)
Background: Local anaesthetics provide relief from pain when applied locally to nerve tissue by blocking conduction of sensory nerve impulse from the receptor to the brain cortex. Objective: This study aimed at evaluating local anaesthetic activity of the methanolic leaves extract of Lannea schimperi. Methods: Six groups of five animals were used; groups I-IV were used for intracutaneous wheal test in guinea pigs for infiltration anaesthesia, while group V and VI were used for guinea pig corneal reflex method of surface anaesthesia. Results: The result indicated a significant (P<0.05) dose dependent local anaesthetic activity of the methanolic leaves extract of Lannea schimperi with faster onset and longer duration of action at 24 mg/ml than at 12 mg/ml of the extract. Additions of 5 μg of adrenaline into the 24 mg/ml preparation also prolonged the duration of local anaesthetic activity of the extract. The extract at 24 mg/ml significantly (P>0.05) inhibited corneal reflex, lidocaine was used as a standard drug in positive control group, while normal saline was used as negative control in all the treated groups. Conclusion: The patent data therefore revealed that the methanolic leaves extract Lannea schimperi possess local anaesthetic principles that may require further scientific elucidation.
Keywords: Lannea schimperi